Putusan Ultra Petita Mahkamah Konstitusi Terkait Judicial Review Syarat Pencalonan Presiden dan Wakil Presiden (Analisis Putusan Mahkamah Konstitusi Nomor 90/PUU-XXI/2023) - Pane, Orin Sabrina; Raharja, Ida Bagus Mahayoga (Jurnal Legislasi Indonesia, 2024)
The Constitutional Court of Indonesia holds significant importance as a judicial authority that evaluates the constitutionality of legislation. However, the Court has been criticized for issuing ultra petita decisions, especially when examining open legal policy norms. This study analyzes Constitutional Court Decision Number 90/PUU-XXI/2023, which expands the eligibility requirements for presidential and vice-presidential candidates. Our research method employs a normative legal approach through the analysis of statutory regulations, conceptual analysis, and case analysis, to identify the limitations of ultra petita application in judicial review and how these limitations are applied in the a quo decision. The research reveals four aspects that limit the Constitutional Judge in issuing ultra petita decisions: (1) the substantive issues requested for examination are related to other articles that form the core of the law under review, (2) the petitioner's petitum includes a request ‘ex aequo et bono’ (the decision is requested to be passed by principles of what is fair and just), (3) the examination of the law involves public interests and is erga omnes in nature, and (4) the decision aims to achieve substantive justice. However, the a quo decision has deviated from these limitations, especially since the subject of the petition is not a legal policy that violates morality, rationality, and intolerable injustice.